Influence of Structural Plane Microscopic Parameters on Direct Shear Strength. (2nd July 2018) - Cheng, Yanhui; Yang, Weijun; He, Dongliang
Abstract : Structural plane is a key factor in controlling the stability of rock mass engineering. To study the influence of structural plane microscopic parameters on direct shear strength, this paper established the direct shear mechanical model of the structural plane by using the discrete element code PFC2D. From the mesoscopic perspective, the research on the direct shear test for structural plane has been conducted. The bonding strength and friction coefficient of the structural plane are investigated, and the effect of mesoscopic parameters on the shear mechanical behavior of the structural plane has been analyzed. The results show that the internal friction angle φ of the structural plane decreases with the increase of particle contact stiffness ratio. However, the change range of cohesion is small. The internal friction angle decreases first and then increases with the increase of parallel bond stiffness ratio. The influence of particle contact modulus EC on cohesion c is relatively small. The internal friction angle obtained by the direct shear test is larger than that obtained by the triaxial compression test. Parallel bond elastic modulus has a stronger impact on friction angle φ than that on cohesion c . Under the same normal stress conditions, the shear strength of the specimens increases with particle size. The shear strength of the specimen gradually decreases with the increase of the particle size ratio.